Multidrug-Resistant Bacteria Isolated From Surgical Site of Dogs, Surgeon's Hands and Operating Room in a Veterinary Teaching Hospital in Brazil - Menezes, Mareliza P. [UNESP]; Borzi, Mariana M.; Ruaro, Mayara A. [UNESP]; Cardozo, Marita V.; Rabelo, Rodrigo C.; Verbisck, Newton V.; Moraes, Paola C. [UNESP] (Elsevier, 2022)
Surgical environment can play as a source of multidrug-resistance organism, what can pose as a big threat to the patients and health care professionals. This study aimed to evaluate the prevalence and antimicrobial resistance profile of Gram-positive cocci (GPC) and Gram-negative bacilli (GNB) isolated from the surgical environment. All samples were collected during the intraoperative period of clean/clean-contaminated (G1) and contaminated (G2) surgery. A total of 150 samples were collected from the superficial surgical site in the beginning (n = 30) and the end (n = 30) of the procedure, surgeon's hands before (n = 30) and after (n = 30) antisepsis, and the surgical environment (n = 30). MALDI-TOF MS and antimicrobial susceptibility testing by disk diffusion method were performed for species identification, and determination of the resistance profile. Sixty-eight isolates of GPC and 15 of GNB were obtained. Staphylococcus spp. were the most frequent species isolated from surgical site (55.26% [21/38]), surgeon's hands (46.15% [6/13]), and environment (56.67% [17/30]). GPC were mostly resistance to penicillin (85.71% [54/63]), and erythromycin (77.78% [49/63]), and GNB were mostly resistance to cefazolin (58.33% [7/12]), and azithromycin (58.33% [7/12]). High incidence of multidrug resistance was observed in coagulase-negative staphylococci (86.21% [25/29]), coagulase-positive staphylococci (86.67% [13/15]), Enterococcus spp. (68.42% [13/19]) and Gram-negative bacilli (60% [9/15]). The high rate of resistance of commensal bacteria found in our study is worrying. Coagulase-negative staphylococci are community pathogens related to nosocomial infections in human and veterinary hospitals, their presence in healthy patients and in veterinary professionals represent an important source of infection in the One Health context. Continuous surveillance and application of antimicrobial stewardship programs are essential in the fight against this threat.
Keywords: antimicrobial resistance; community pathogen; enterobacteria; Enterococcus spp; methicillin-resistant Staphylococcus; surgical environment